Tunable circularly polarized luminescence of sol-gels based on chiral cyclometalated platinum(II) complexes. (May 2022) - Zhang, Hua-Hong; Jing, Jing; Wu, Shui-Xing; Luo, You-Ping; Sun, Shi-Shu; Zhang, Da-Shuai; Shi, Zai-Feng; Zhang, Xiao-Peng
Abstract: Two couples of enantiomeric pinene-containing N^C^N and C^N^N-coordinated Pt(II) isocyanide complexes decorated with long alkyl chains have been prepared and characterized. Complexes (−)-1 and (−)-2 form chiral ordered self-assemblies through Pt⋅⋅⋅Pt, π − π, and hydrophobic-hydrophobic interactions in nonpolar solvents, which is manifested by scanning electron and confocal microscope studies. Complexes (−)-1 and (−)-2 display appreciable aggregation-induced emission enhancement behavior in the CH2 Cl2 / n -hexane system with the emission quantum yield ( Φ em ) intensified by a factor of twenty. The complexes exhibit thermo-responsive sol-to-gel transition and solvent-tuned emission colors in higher alcohols or alkane solvents. Considerable circularly polarized luminescence (CPL) signals deriving from chiroptically active 3 MMLCT transition with the g lum value of 10 −2 order have been found for most sols at RT. Despite minor structural variations in complexes (−)-1 and (−)-2, the CPL activity of Pt(N^C^N) isocyanide complex (−)-1 is more sensitive to solvent and temperature. In contrast, the CPL activity of Pt(N^N^C) isocyanide complex (−)-2 is inert to external factors. This research provides a new design strategy for developing tunable CPL platinum(II) complex sol-gels. Graphical abstract: Image 1 Highlights: Two couples of Pt(II) isocyanide complexes decorated with long alkyl chains have been prepared. Sol-gels have been generated in nonpolar solvents. All complexes exhibit prominent aggregation-induced enhancement of emission. Minor structural variations lead to different tunabilities on circularly polarized luminescence.